Analytical characterization of coformulated antibodies as combination therapy - Jun Kim (mAbs, 2020)
When two therapeutic agents are combined in a single formulation, i.e., coformulated, the quality and safety of the individual agents must be preserved. Here we describe an approach to evaluate the quality attributes of two individual monoclonal antibodies (mAbs), designated mAb-A and mAb-B, in coformulation. The mAbs were fractionated from heat-stressed coformulated drug product (DP) by hydrophobic interaction chromatography. Each purified mAb fraction was then compared with mAb-A and mAb-B in their individual formulations from the same drug substance sources used to make the coformulated DP lot, which was subjected to the same stress conditions. Product variants were evaluated and compared by using several analytical tests, including high-performance size exclusion chromatography (HPSEC), reducing and nonreducing gel electrophoresis, ion-exchange chromatography, capillary isoelectric focusing, and peptide mapping with mass spectrometry. Intermolecular interactions in coformulated and photostressed DPs were studied by evaluating aggregates fractionated from coformulated DP by HPSEC. Aggregate fractions of coformulated DP contained dimers, but not coaggregates, of mAb-A or mAb-B. Moreover, extensive assays for higher-order structure and biological interactions confirmed that there was no interaction between the two mAb molecules in the coformulation. These results demonstrate that the two coformulated therapeutic mAbs had the same quality attributes as the individually formulated mAb-A and mAb-B, no new quality attributes were formed, and no physicochemical, intermolecular, or biological interactions occurred between the two components. The approach described here can be used to monitor the product quality of other coformulated antibodies.